KINERJA KEPALA SEKOLAH DALAM MENINGKATKAN MUTU LULUSAN PADA MADRASAH TSANAWIYAH NEGERI MEUREUBO - Muzakar Muzakar (Islam Futura, 2014)
The performance of the school head master is one of the efforts of the school head master to improve the graduate quality. The aim of this research is to describe the work of the school head master in improving the students' quality of MTsN Meurebo. The method of the study is descriptive method through qualitative approach. The data collection techniques are: observations, interviews and documentations. The subjects of the research are: the school head master, school administrative chairman, teachers. The result of the study shows that: 1) the ability of school headmaster in improving the quality of the graduates is met the graduate criteria because the school head master has run various abilities to support the achievement of the graduates' quality, both abilities as an educator, manager, administrator, supervisor, leader, and innovator . 2), In practice , it is indeed need motivation of the school head master and all the school members to manifest the graduates quality. 3), the school head master is able to identify the strengths, weaknesses, opportunities and threats faced by the school, so that it can be used as a reference in making decisions concerning the improvement of the quality of graduates. In its implementation that various efforts require s a consensus commitment of all the school members in order to achieve the optimal quality of the school graduates.